Statute of the society for the care of poor jewish children in Kolomyia (1908): historical and legal analysis - Аракелян, Мінас Рамзесович; Аракелян, М. Р.; Аракелян, Минас Рамзесович; Arakelian, Minas R.; Arakelian, Minas; Левченко, Інна Миколаївна; Левченко, І. М.; Левченко, Инна Николаевна; Levchenko, Inna M.; Levchenko, Inna (Дрогобич : Дрогоб. держ. пед. ун-т ім. І. Франка, 2020)
The purpose of the article is to publish and analyze the Statute of the Society for the Care of Poor Jewish Children in Kolomyia (1908) as a source for the history of this Society and the legal culture of the Jewish community in the eastern cities of Eastern Galicia in the early 20th century. The research methodology – principles of scientific, objectivity, historicism, methods of external and internal critique of sources. The research novelty is that the Statute of the Society for the Care of Poor Jewish Children in Kolomyia (1908) was first published and analyzed as a historical and historical-legal source. The Conclusions. Thus, the Statute of the Society for the Care of Poor Jewish Children, which was formed in Kolomyia in 1908, is supposed to have been concluded by the Jewish lawyer H. Landau. After approval by the Governor, the Society published its Statute, which consisted of 29 articles. This document is known to researchers, but has never been published or analyzed as a historical and legal source. It is stored in the Central State Historical Archive of Ukraine in Lviv. The Statute had a bifunctional purpose, as it regulated the activities of the Society and the “Okhoronka” formed by it. Articles of the Statute can be divided into three groups: 1) the purpose and material principles of the Society and the “Okhoronka”; 2) tasks, rights and responsibilities of the members of the Society and the “Okhoronka”; 3) structural-organizational and managerial aspects of activity of the Society and the “Okhoronka”. We consider the Statute to be an important historical source for the history of Jewish public organizations of charitable orientation in Eastern Galicia, the history of Kolomyia in the early 20th century, as well as the history of domestic legal thought. The document is published in the original language (Polish) in compliance with the necessary archaeographic requirements.

Анотація. Мета статті – опублікувати та проаналізувати статут Товариства по догляду за бідними єврейськими дітьми у Коломиї (1908) як джерело до історії зазначеного Товариства та правової культури єврейської громадськості повітових міст Східної Галичини початку ХХ ст. Методологія дослідження – принципи науковості, об’єктивності, історизму, методи зовнішньої та внутрішньої критики джерел. Наукова новизна полягає у тому, що уперше публікується Статут Товариства по догляду за бідними єврейськими дітьми у Коломиї (1908) та здійснюється його аналіз як історичного та історико-правового джерела. Висновки. Отже, Статут Товариства по догляду за бідними єврейськими дітьми, яке утворилося в Коломиї 1908 р., припускаємо, було укладено єврейським юристом Г. Ландау. Після затвердження Намісництвом, Товариство надрукувало свій Статут, який складався з 29 статей. Цей документ відомий дослідникам, але жодного разу не публікувався та не аналізувався як історико-правове джерело. Він зберігається у Центральному державному історичному архіві України у Львові. Статут мав біфункціональне призначення, оскільки регламентував діяльність Товариства та утвореної ним охоронки. Статті Статуту умовно можна поділити на три групи: 1) мета і матеріальні засади функціонування Товариства й охоронки; 2) завдання, права і обов’язки членів Товариства і охоронки; 3) структурно-організаційні та управлінські аспекти діяльності Товариства та охоронки. Вважаємо Статут важливим історичним джерелом до історії єврейських громадських організацій харитивного спрямування у Східній Галичині, історії Коломиї початку ХХ ст., а також до історії вітчизняної правової думки.

Аннотация. Цель статьи - опубликовать и проанализировать устав Общества по уходу за бедными еврейскими детьми в Коломии (1908) в качестве источника к истории указанного Общества и правовой культуры еврейской общественности уездных городов Восточной Галичины начала ХХ в. Методология исследования - принципы научности, объективности, историзма, методы внешней и внутренней критики источников. Научная новизна заключается в том, что впервые публикуется Устав Общества по уходу за бедными еврейскими детьми в Коломии (1908) и осуществляется его анализ как исторического и историко-правового источника. Выводы. Итак, Устав Общества по уходу за бедными еврейскими детьми, которое образовалось в Коломии 1908 г., предполагаем, был составлен еврейским юристом Г. Ландау. После утверждения наместничества, Общество опубликовало свой Устав, состоящий из 29 статей. Этот документ известен исследователям, но ни разу не публиковался и не анализировался как историко-правовой источник. Он хранится в Центральном государственном историческом архиве Украины во Львове. Устав имел бифункциональное назначение, поскольку регламентировал деятельность Общества и образованной им "охоронки". Статьи Устава условно можно разделить на три группы: 1) цель и материальные основы функционирования общества и "охоронки"; 2) задачи, права и обязанности членов Общества и охранки; 3) структурно-организационные и управленческие аспекты деятельности Общества и "охоронки". Считаем Устав важным историческим источником для истории еврейских общественных организаций харитивного направления в Восточной Галиции, истории Коломии начала ХХ в., а также истории отечественной правовой мысли.
Levchenko I. Statute of the society for the care of poor jewish children in Kolomyia (1908): historical and legal analysis / I. Levchenko, M. Arakelian // Східноєвропейський історичний вісник. – Дрогобич : Дрогоб. держ. пед. ун-т ім. І. Франка, 2020. – Вип. 15. – С. 80-92.
Keywords: The Society for the Care of Poor Jewish Children; “Okhoronka”; Eastern Galicia; Kolomyia; assimilation; Jewish community; товариство по догляду за бідними єврейськими дітьми; охоронка; Східна Галичина; Коломия; асиміляція; єврейська громада; общество по уходу за бедными еврейскими детьми; "Охоронка"; Восточная Галичина; Коломия; ассимиляция; еврейская община; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects; Research Subject Categories::LAW/JURISPRUDENCE